The Effect Of Mangrove Leaf Extract Dosage Sonneratia Alba On Hela Cell Viability - Fitria Devi Suryaningrum (Journal of Stem Cell Research and Tissue Engineering, 2021)
Cervical cancer is caused due to infection from the Human Papilloma Virus (HPV) which attacks the sexually active female reproductive organs. Treatment is carried out alternatively using natural ingredients such as mangroves. Sonneratia alba is a type of mangrove plant that has been used in alternative medicine because of its potential as an anticancer. This study aims to determine the effect of Sonneratia alba mangrove extract on heLa cell viability. The Sonneratia alba leaf powder was extracted using stratified maceration. The solvents used include n-hexane, ethyl acetate, and ethanol. The results showed that the LC50 value was 3.59 ppm, this means that the ethyl acetate extract has toxic properties. Phytochemical test results of Sonneratia alba leaf extract contain alkaloid compounds, steroids / triterpenoids, and tannins. The results of the test yield extract were 12.60%, extract water content was 21.24%, and total phenol was 504.08 mg / g GAE Test The results of the LC-MS test resulted in the suspicion of compounds including diosmetin, caffeine, and turmeron. The ethyl acetate extract of Sonneratia alba leaves was cytotoxic against heLa cell viability with the resulting IC50 value of 478.630 µg / mL